Forest and communities. Deforestation, Conservation and Socio-ecological Relations in the Mau Forest, Kenya - Albertazzi, Stefania (Milano University Press, 2023)
The book analyzes the case of Mau Forest (Kenya), exploring the deforestation process that has occurred and the controversial and changing relationships between a protected forest and the communities living within and around its borders. The volume contributes to the international debate on political ecology from a predominantly geographical perspective, enriched by contributions more closely related to the natural sciences. The study is based on a multi-year research (2017-22) that combines qualitative and quantitative methodologies: research in archives and government offices, field studies in the forest area, semi-structured interviews, participatory mapping with local community members, and satellite and drone remote sensing.